Analisis Hukum Perlindungan Konsumen Terhadap Praktik Greenwashing dalam Perspektif Perdata Indonesia - Chesa Wastsaljideri; Nuzul Rahmayani (LPPM Institut Pendidikan Nusantara Global, 2026)
This research examines greenwashing practices in the context of civil law and consumer protection in Indonesia, which emerged as a response to increasing public environmental awareness accompanied by the prevalence of misleading eco-friendly claims. These practices cause economic losses to consumers, diminish public trust, and create legal problems that need to be addressed. Using a normative juridical method through a literature approach, the research examines laws and regulations, legal literature, journals, and court decisions to analyze the concept of greenwashing, its position under the Consumer Protection Law, and the forms of civil legal liability for businesses. The research findings indicate that greenwashing violates the principles of good faith, balance, and propriety, and can be categorized as product liability based on information defects, requiring businesses to provide compensation, contract cancellation, or other remedies to consumers. This research emphasizes the importance of strengthening regulations and consumer protection mechanisms to ensure honest, transparent, and sustainable business practices.